Therapeutic Efficacy of Curcumin Enhanced by Microscale Discoidal Polymeric Particles in a Murine Asthma Model - Jun Young Park; Ga Eul Chu; Sanghyo Park; Chaewon Park; Susmita Aryal; Won Jun Kang; Won Gil Cho; Jaehong Key (MDPI AG, 2020)
Curcumin is considered a potential anti-asthmatic agent owing to its anti-inflammatory properties. The objective of the present study was to prepare curcumin-containing poly(lactic-co-glycolic acid)-based microscale discoidal polymeric particles (Cur-PLGA-DPPs) and evaluate their anti-asthmatic properties using a murine asthma model. Cur-PLGA-DPPs were prepared using a top-down fabrication method. The prepared Cur-PLGA-DPPs had a mean particle size of 2.5 ± 0.4 μm and a zeta potential value of −34.6 ± 4.8 mV. Ex vivo biodistribution results showed that the Cur-PLGA-DPPs mainly accumulated in the lungs and liver after intravenous injection. Treatment with Cur-PLGA-DPPs effectively suppressed the infiltration of inflammatory cells in bronchoalveolar lavage fluid, and reduced bronchial wall thickening and goblet-cell hyperplasia compared to those in the phosphate-buffered-saline-treated control group. No significant changes in hematology and blood biochemistry parameters were observed after treatment with Cur-PLGA-DPPs. At equal curcumin concentrations, treatment with Cur-PLGA-DPPs exhibited better therapeutic efficacy than treatment with free curcumin. Our results suggest that the microscale Cur-PLGA-DPPs can be potentially used as a lung-targeted asthma therapy.